A model of damaged medium for evaluating the durability of structures subjected to combined low- and high-cycle fatigue loading - Volkov, Ivan Andreevich; Ereev, Mikhail Nickolaevich; Korotkikh, Yurii Georgievich; Tarasov, Ivan Sergeevich (Computational Continuum Mechanics, 2012)
In order to evaluate the strength and lifetime of critical engineering structures, we have developed a mathematical model of damaged medium consisting of elastoplastic constitutive equations, kinetic equations of damage accumulation, and a strength criterion of damaged material. A version of the evolution equation describing accumulation of damages caused by a combination of low-cycle fatigue (LCF) and high-cycle fatigue (HSF) mechanisms is proposed. It is shown that under regular cyclic loading, when the amplitude of deformation in a cycle decreases, the transition from low cycle fatigue to high cycle fatigue proceeds gradually and depends on the physical interaction of these mechanisms in the transition zone. A method for determining the parameters of the evolution equation of fatigue damage accumulation is presented. Comparison of the calculated and experimental data shows that the developed model of damage medium adequately describes the durability of structures subjected to combined low- and high-cycle fatigue loading.
Keywords: modeling; stress-strain state; plasticity; damage; failure; low-and high-cycle fatigue; durability; resource